RISK OF FMF DEVELOPMENT AMONG HETEROZYGOUS PATIENTS IN ARMENIAN POPULATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
aim of this study is the investigation of one mutation carriers of MEFV gene among Armenian population. We designed and established the genetic register for proper collection of patients’ data including their ethnicity, clinical and laboratory data, as well as family cases. According to the results the frequency of FMF inheritance with only one mutation of MEFV gene among Armenian population is about 17.5% and by autosomal-recessive mode (homozygous or compound-heterozygous) is 82.5%.
Keywords: familial Mediterranean fever, MEFV gene mutations, pseudodominant inheritance